Konstruksi Pendidikan Islam Berbasis Moderasi Beragama Pada Masyarakat Multireligi Di Kelurahan Perak Barat Surabaya - Adhima, Putri Nur; Farih, Muhammad (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This study aims to find out how the construction of Islamic education based on religious moderation in the multireligious community of Perak Barat Village, Surabaya. In the context of religious diversity, the local community has succeeded in building a harmonious and peaceful life through the values of tolerance. This research uses qualitative research with a case study approach. The results of the study show that through Peter L Berger's theory of social construction, moderation values such as tolerance, mutual respect, and peaceful coexistence have been firmly formed in the life of the Community. The construction process takes place through three main stages: externalization, objectification, and internalization. The value of moderation is not only taught formally, but is also revived in social practices such as mutual cooperation activities, interfaith activities, religious celebrations, and value education from an early age. This process succeeded in fostering collective awareness and forming the character of an open, peaceful, and tolerant society. Such Islamic education is an important foundation in strengthening harmony between religious communities in the midst of diverse societies.